BORDERS AND INTEGRATION: BECOMING A BOSNIAN-AMERICAN - ADNA KARAMEHIC-OATES; AJLINA KARAMEHIC-MURATOVIC (Washington University Global Studies Law Review, 2020)
For Bosnian and Herzegovinians fleeing the conflict in their homeland in the 1990s, the process of finding a safe haven was a tumultuous experience. Despite the protections outlined in the 1951 Geneva Convention, the response of former Yugoslavia’s neighboring countries to the humanitarian crisis was a tightening of borders and restrictive reception policies. These experiences are in contrast to the reception policies Bosnian refugees encountered in the United States, whose permanent resettlement program at that period in time offered opportunities for ‘normal life,’ as discussed by Jansen1. ‘Border work,’ using Jones and Johnson’s2 term, has implications for practical forms of integration. This paper reviews and contrasts the ‘border work’ of European nations and the United States in relation to Bosnian refugees and discusses the integration of Bosnian-Americans in the United States, using St. Louis, Missouri, as an example. With the focus on the Bosnian community in the United States, particularly in cities with many Bosnians, studying the US Bosnian diaspora makes for an interesting case study provided that in terms of social, cultural, and economic adaptation, the Bosnian story is considered an immigration success story. The paper has implications for practical forms of integration, resettlement, and adaptation.
Keywords: iMMIGRATION; BORDER; BOSNIAN-AMERICAN; INTEGRATION